The Complexity of Fungal β-Glucan in Health and Disease: Effects on the Mononuclear Phagocyte System - Camilli, Giorgio; Tabouret, Guillaume; Quintin, Jessica (Frontiers in Immunology, 2018)
β-glucan, the most abundant fungal cell wall polysaccharide, has gained much attention from the scientific community in the last few decades for its fascinating but not yet fully understood immunobiology. Study of this molecule has been motivated by its importance as a pathogen associated molecular pattern upon fungal infection as well as by its promising clinical utility as biological response modifier for the treatment of cancer and infectious diseases. Its immune effect is attributed to the ability to bind to different receptors expressed on the cell surface of phagocytic and cytotoxic innate immune cells, including monocytes, macrophages, neutrophils and NK cells. The characteristics of the immune responses generated depend on the cell types and receptors involved. Size and biochemical composition of β-glucans isolated from different sources affect their immunomodulatory properties. The variety of studies using crude extracts of fungal cell wall rather than purified β-glucans renders data difficult to interpret. A better understanding of the mechanisms of purified fungal β-glucan recognition, downstream signalling pathways and subsequent immune regulation activated, is therefore essential to develop new antifungal therapy but also to evaluate β-glucan as a putative anti-infective and anti-tumour mediator. Here, we briefly review the complexity of interactions between fungal β-glucans and mononuclear phagocytes during fungal infections. Furthermore, we discuss and present available studies suggesting how different fungal β-glucans exhibit antitumor and antimicrobial activities by modulating the biologic responses of mononuclear phagocytes, which make them potential candidates as therapeutic agents.